Ekolojik niş modellemesi ile iki endemik stenus türünün (coleoptera: staphylınıdae: stenınae) iklim değişikliğinin etkileri üzerine değerlendirilmesi - TURAN, YAVUZ (My University, 2022)
Bu çalışma kapsamında Türkiye’de endemik olan iki Stenus Latreille, 1797 (Coleoptera: Staphylinidae: Steninae) türü için Ekolojik Niş Modellemesi (ENM) MaXent yazılımı kullanılarak yapılmış ve günümüzde ve gelecekte iklim değişikliğine bağlı olarak türlerin dağılımı için uygun habitatlar belirlenmiştir. 2050 ve 2070 yıllarında türlerin dağılımına uygun habitatların belirlenmesi için Hükümetler Arası İklim Paneli (IPCC) 5. raporunda belirlenen iklim değişikliği senaryoları (RCP26, RCP45, RCP60, RCP85) kullanılmıştır.

Within the scope of this study, Ecological Niche Modeling (ENM) applied using MaXent software for two Stenus Latreille, 1797 (Coleoptera: Staphylinidae: Steninae) species, which are endemic in Turkey. Current suitable habitats for the distribution of the species and future habitats due to climate change were determined. The climate change scenarios (RCP26, RCP45, RCP60, RCP85) determined in the 5th report of the Intergovernmental Panel on Climate Change (IPCC) were used to determine the habitats suitable for the distribution of species in 2050 and 2070.
Evaluation of two endemic stenus species (coleoptera: staphylinidae: steninae) on the effects of climate change by ecological nice modeling